Evaluation of Maharah Kitabah Learning in Class 8A1 at MTs Negeri 2 Surakarta Based on the Countenance Stake Model - Ummu Hanifah; Maslamah Maslamah; Nanang Qosim (Lembaga Penelitian dan Pendidikan Mandala, 2026)
This study aims to evaluate the effectiveness of Arabic language learning (writing skills/maharah kitabah) in class 8A1 at MTs Negeri 2 Surakarta using the Stake’s Countenance Model. This model consists of three main components: antecedents (planning), transactions (implementation), and outcomes (learning results). The research employed a descriptive qualitative evaluative approach. Data were collected through observations, written tests, and documentation, then analyzed using contingency analysis to compare the ideal and actual conditions, accompanied by judgments regarding their level of conformity. The findings show that in the planning component, the teacher demonstrated good readiness through complete learning tools, although media innovation and the use of technology still need improvement. In terms of implementation, the learning process ran effectively and according to plan; however, time management needs to be improved to ensure more optimal activities. In the outcome component, students' writing abilities showed strong achievement, particularly in imla’ and insya’. The contingency analysis also revealed a strong relationship between planning readiness and successful learning outcomes. Overall, the effectiveness of maharah kitabah learning in class 8A1 can be categorized as good, although several improvements are still needed to enhance the quality of future learning.